SISTEM PAKAR PENDETEKSI KERUSAKAN HANDPHONE BLACKBERRY PADA JOJO CELL BSD - TANGERANG - Kristian Piet Nugroho; Imron (LPPM STMIK Antar Bangsa, 2015)
Abstract–The role of technology is to support the performance of a company. Advances in information technology that is increasingly sophisticated, especially in the field of mobile technology able to support a person in performing duties and become more efficient and mobile. With the rapid development on the mobile device must be balanced with a software that is able to provide information to the user of a mobile device to find out about the possibilities of damage that might occur in these devices. Damage detection expert system is a mobile phone software that is able to provide information about the possible damage that could occur on the mobile phone to mobile device users. Jojo cell is a company engaged in mobile phone service center. With all the information and knowledge that experts possess is then implemented in an expert system detecting damage to mobile phone users is expected that mobile devices can know with certainty the type of damage that occurred on the device when the cell Jojo took it to a technician without having much to ask the technicians.